دراسة تراكيز حمض الفيتيك في بعض الأغذية المستهلكة في مدينة اللاذقية - ياسين, مفيد (Latakia University Journal -Basic Sciences Series, 2013)
تمت هذه الدراسة على بعض الخضار والفواكه المحلية قبل وبعد النضج (تفاح, خوخ, دراق, جنرلك, بندورة) والبقوليات الخضراء والمجففة (فول, حمص, عدس, بازلاء, لوبياء) والبذور الزيتية (فول سوداني, سمسم, ذرة) والحبوب ومنتجاتها (قمح, شعير, شوفان, رز مستورد, طحين وخبز بأنواعهما, نخالة, برغل) المستهلكة في مدينة اللاذقية، وتبين بأن أغلب هذه المنتجات تحتوي على مستويات عالية من حمض الفيتيك ولاسيما المنتجات غير الناضجة (0.15-3.57 غ%غ.م.ج) ومشتقاتها (0-1.95 غ%غ.م.ج) This study is carried out to determine phytic acid in some local vegetables and fruits, before and after ripening (apples, peaches, pean, tomato), green and dried legumes (beans, chickpea, lentil, peas, soybean, maize ….), and oil seeds (peanut, sesami, ……) and cereals and their products (grain, barley, oats, rice, bread kinds, bran, borghol) that are consumed in Latakia city. Most of the products contain high levels of phytic acid, especially in green products and their derivatives; the values range between (0.1-3.57 %) and (0-1.95 %) on dry bases respectively.